Corporate governance and information asymmetry among UAE listed companies - Bajrei, Saleh Salem Saeed; Lode, Nor Asma (2013)
This study investigates the relationship between corporate governance mechanism. board size, board independence, duality, board meetings, and director's ownership and audit committee size with the level of information asymmetry, while board independence, board meetings, directors' ownership and audit committee size are negative associated to information asymmetry.The findings indicate that board size is unable to monitor the management and protect the interest of shareholders.Nevertheless, audit committee, director's ownership and board independence are significant corporate governance mechanisms in protecting the interest of shareholders.